The culture of capital punishment in Japan - Johnson, David T. (Palgrave advances in criminology and criminal justice in Asia, 2020)
This open access book provides a comparative perspective on capital punishment in Japan and the United States. Alongside the US, Japan is one of only a few developed democracies in the world that retains capital punishment and continue to carry out executions on a regular basis. There are some similarities between the two systems of capital punishment but there are also many striking differences which are explored within this study. These include differences in capital jurisprudence, execution method, the nature and extent of secrecy surrounding death penalty deliberations and executions, institutional capacities to prevent and discover wrongful convictions, orientations to lay participation and to victim participation, and orientations to “democracy” and governance. Johnson also examines and explores several fundamental issues about the ultimate criminal penalty, such as whether is death different from other criminal sanctions, what is the proper role of citizen preferences in governing a system of punishment and why do the feelings of victims and survivors matter?